NANOCOMPOSITE BASED ON HYDROXYAPATITE AND SILVER WITH ANTIBACTERIAL ACTIVITY - MOCANU, Aurora; FLOREA, Diana Alexandra; TOMOAIA, Gheorghe; POP, Lucian-Cristian; DANISTEAN, Ancuta; RAPUNTEAN, Sorin; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2023)
A nanocomposite made from hydroxyapatite (HAP) and silver nanoparticles (AgNPs), namely HAP-4.5 wt% AgNPs, is reported. HAP was prepared using a wet precipitation technique, and AgNPs were made by reducing silver nitrate with glucose in basic medium. HAP, AgNPs and HAP-4.5 wt% AgNPs composite were characterized by X-ray diffraction (XRD), SEM - energy dispersive X-ray spectroscopy (EDS) and different imagistic methods: TEM and AFM. The antibacterial effect of the HAP-4.5 wt% AgNPs nanocomposite was tested using diffusion technique in nutritive agar on two pathogenic species, one Gram-negative (Salmonella typhimurium) and one Gram-positive (Bacillus cereus) and promising results were obtained. This hydroxyapatite-silver nanocomposite can be employed as a potential antimicrobial coating for dental and orthopedic implants, or they can be utilized such as bone cements in clinical procedures.